A liver-targeting Cu(i) chelator relocates Cu in hepatocytes and promotes Cu excretion in a murine model of Wilson's disease. Issue 6 (13th May 2020) - Monestier, Marie; Pujol, Anaïs M.; Lamboux, Aline; Cuillel, Martine; Pignot-Paintrand, Isabelle; Cassio, Doris; Charbonnier, Peggy; Um, Khémary; Harel, Amélie; Bohic, Sylvain; Gateau, Christelle; Balter, Vincent; et al.
Abstract : A hepatocyte-targeting chelator promotes Cu biliary excretion, hence restoring the physiological Cu detoxification pathway in a murine Wilson's disease model. Abstract : Copper chelation is the most commonly used therapeutic strategy nowadays to treat Wilson's disease, a genetic disorder primarily inducing a pathological accumulation of Cu in the liver. The mechanism of action of Chel2, a liver-targeting Cu(i ) chelator known to promote intracellular Cu chelation, was studied in hepatic cells that reconstitute polarized epithelia with functional bile canaliculi, reminiscent of the excretion pathway in the liver. The interplay between Chel2 and Cu localization in these cells was demonstrated through confocal microscopy using a fluorescent derivative and nano X-ray fluorescence. The Cu(i ) bound chelator was found in vesicles potentially excreted in the canaliculi. Moreover, injection of Chel2 either intravenously or subcutaneously to a murine model of Wilson's disease increased excretion of Cu in the faeces, confirming in vivo biliary excretion. Therefore, Chel2 turns out to be a possible means to collect and excrete hepatic Cu in the faeces, hence restoring the physiological pathway.